2018
DOI: 10.1055/s-0038-1676289
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes in Pregnancies affected by Bone and Soft Tissue Tumors

Abstract: Objective  This study was aimed to describe perinatal outcome of a cohort of pregnant patients with bone and soft tissue tumors and to compare the current series with our group's previously reported experience. Methods  Pregnant women diagnosed before and during pregnancy were identified, retrospectively, for the years 2004 to 2014. Relevant maternal and neonatal data were collected. Results  Forty-eight patients were identified. Ten cases were diagnosed during pregnancy. Pelvis, abdomen, and extremities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
1
21
0
2
Order By: Relevance
“…We found a non-significantly increased mortality for women with lung cancer diagnosed during pregnancy but not if diagnosed postdelivery. In line with previous reports, we found no increased mortality in women with pregnancy-associated bone/soft-tissue sarcoma [38]. However, in women with gynecological sarcomas diagnosed after delivery we found a worse prognosis, to our knowledge not previously reported [39].…”
Section: Discussionsupporting
confidence: 92%
“…We found a non-significantly increased mortality for women with lung cancer diagnosed during pregnancy but not if diagnosed postdelivery. In line with previous reports, we found no increased mortality in women with pregnancy-associated bone/soft-tissue sarcoma [38]. However, in women with gynecological sarcomas diagnosed after delivery we found a worse prognosis, to our knowledge not previously reported [39].…”
Section: Discussionsupporting
confidence: 92%
“…10 According to Figueiro-Filho et al, preterm birth and fetal growth restriction were common associations. 11 In this study preterm birth was seen but fetal growth restriction was not seen. Chemotherapeutic agents like Vincristine, Adriyamicin and Cyclophosphamide was used for one woman during pregnancy.…”
Section: Discussionmentioning
confidence: 46%
“…However, the number of patients included in these studies was relatively small. [17,18] Therefore, the implication of chemotherapy to cancer patients complicated by pregnancy may be underappreciated, and whether chemotherapy would increase the risk of maternal deaths still requires more large-scale and in-depth populationbased researches. The observed number of deaths represents the total number of maternal deaths in patients with cancer recorded during the study period; the expected number represents the number of individuals who have maternal deaths in the general population with a similar distribution of age, race, and origin.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian survey of women diagnosed with bone and soft tissue tumors before and during pregnancy and a study on epithelial ovarian cancer indicated that considering the maternal mortality rate, chemotherapy must be evaluated for each woman on a case-by-case basis. However, the number of patients included in these studies was relatively small [17,18] . Therefore, the implication of chemotherapy to cancer patients complicated by pregnancy may be underappreciated, and whether chemotherapy would increase the risk of maternal deaths still requires more large-scale and in-depth population-based researches.…”
Section: Discussionmentioning
confidence: 99%